Establishment of a droplet digital PCR detection method for Vp4 gene of PoRV - Tan, Xinwei; Zheng, Xiaoyu; Zou, Guangyuan; Ma, Manxin; Yuan, Ze; Lang, Gong; Zhang, Guihong (Frontiers in Veterinary Science, 2026)
Diarrhea outbreaks in pigs occur most frequently during winter, porcine rotavirus (PoRV) is one of the important diarrheal diseases. Droplet digital polymerase chain reaction (DDPCR), a detection method that can perform absolute quantification of genes. The study aimed to diagnose PoRV infection using a probe-based DDPCR. 10 2-day-old piglets with mild diarrhea were obtained from a commercial pig farm. No PoRV was detected in the anal swab using colloidal gold test strips. To verify the results of the colloidal gold test strips, RT-qPCR was performed, which identified PoRV in six piglets. Given the limited sensitivity of colloidal gold test strips and RT-qPCR, we developed a DDPCR assay targeting the PoRV Vp4 gene for enhanced detection. The DDPCR assay demonstrated optimal performance at a primer:probe concentration of 400:400 nM and an annealing temperature of 57 °C. It achieved a minimum detection limit of 0.21 copies/μL, the detection sensitivity has been enhanced by 100 times compared to RT-qPCR. Using the established DDPCR detection method, the four samples that tested negative by RT-qPCR were re-tested, and all were found to be PoRV-positive, indicating that the sensitivity of DDPCR was higher than that of RT-qPCR. This study highlights its potential as a valuable tool for early clinical diagnosis and disease control in piglets.